Social context and perspectives of non-medical prescription opioid use among young adults in Rhode Island: A qualitative study. - Yedinak, Jesse L; Kinnard, Elizabeth N; Hadland, Scott E; Green, Traci C; Clark, Melissa A; Marshall, Brandon D L (The American journal on addictions, 2016)
This pilot study examined the context of nonmedical prescription opioid (NMPO) use and related risk behaviors among young adults in Rhode Island, a New England region with markedly high prevalence of NMPO use and overdose mortality.